Airborne Lidar Measurements of XCO2 in Synoptically Active Environment and Associated Comparisons With Numerical Simulations. Issue 16 (17th August 2022) - Walley, Samantha; Pal, Sandip; Campbell, Joel F.; Dobler, Jeremy; Bell, Emily; Weir, Brad; Feng, Sha; Lauvaux, Thomas; Baker, David; Blume, Nathan; Erxleben, Wayne; Fan, Tai‐Fang; et al.
Abstract: Frontal boundaries have been shown to cause large changes in CO2 mole‐fractions, but clouds and the complex vertical structure of fronts make these gradients difficult to observe. It remains unclear how the column average CO2 dry air mole‐fraction (XCO2 ) changes spatially across fronts, and how well airborne lidar observations, data assimilation systems, and numerical models without assimilation capture XCO2 frontal contrasts (ΔXCO2, i.e., warm minus cold sector average of XCO2 ). We demonstrated the potential of airborne Multifunctional Fiber Laser Lidar (MFLL) measurements in heterogeneous weather conditions (i.e., frontal environment) to investigate the ΔXCO2 during four seasonal field campaigns of the Atmospheric Carbon and Transport‐America (ACT‐America) mission. Most frontal cases in summer (winter) reveal higher (lower) XCO2 in the warm (cold) sector than in the cold (warm) sector. During the transitional seasons (spring and fall), no clear signal in ΔXCO2 was observed. Intercomparison among the MFLL, assimilated fields from NASA's Global Modeling and Assimilation Office (GMAO), and simulations from the Weather Research and Forecasting‐—Chemistry (WRF‐Chem) showed that (a) all products had a similar sign of ΔXCO2 though with different levels of agreement in ΔXCO2 magnitudes among seasons; (b) ΔXCO2 in summer decreases with altitude; and (c) significant challenges remain in observing and simulating XCO2 frontal contrasts. A linear regression analyses between ΔXCO2 for MFLL versus GMAO, and MFLL versus WRF‐Chem for summer‐2016 cases yielded a correlation coefficient of 0.95 and 0.88, respectively. The reported ΔXCO2 variability among four seasons provide guidance to the spatial structures of XCO2 transport errors in models and satellite measurements of XCO2 in synoptically‐active weather systems. Key Points: First airborne observations of column average CO2 dry‐air mole‐fraction (XCO2 ) changes across fronts observed during ACT‐A are reported XCO2 frontal structures compare reasonably well with Weather Research and Forecasting—Chemistry and an in situ data driven assimilation system Results reveal that the differences across models and data were generally much smaller than the magnitude of XCO2 frontal contrasts